2019
DOI: 10.3390/su11215983
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Footprints and Consumer Lifestyles: An Analysis of Lifestyle Factors and Gap Analysis by Consumer Segment in Japan

Abstract: Addressing the prevailing mode of high-carbon lifestyles is crucial for the transition towards a net-zero carbon society. Existing studies fail to fully investigate the underlining factors of unsustainable lifestyles beyond individual determinants nor consider the gaps between current footprints and reduction targets. This study examines latent lifestyle factors related to carbon footprints and analyzes gaps between decarbonization targets and current lifestyles of major consumer segments through exploratory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…Similarly, few would have anticipated living life so physically distanced and socially isolated, except for groups like the elderly. Overnight isolation turned into a new social norm; if it is true that living alone rewards individuals with lower contagion odds, it also represents a regression in sustainability terms as single resident units have a higher carbon footprint than shared living ( Koide et al., 2019 ; ( Williams, 2002 )). These movements combined anticipate that activities previously performed out-of-home will now be entirely home-based, while social ties and social life are circumscribed to a smaller and more intimate circle of trusted (clean-reliable) contacts.…”
Section: Accelerating Decelerating and Innovative Trendsmentioning
confidence: 99%
“…Similarly, few would have anticipated living life so physically distanced and socially isolated, except for groups like the elderly. Overnight isolation turned into a new social norm; if it is true that living alone rewards individuals with lower contagion odds, it also represents a regression in sustainability terms as single resident units have a higher carbon footprint than shared living ( Koide et al., 2019 ; ( Williams, 2002 )). These movements combined anticipate that activities previously performed out-of-home will now be entirely home-based, while social ties and social life are circumscribed to a smaller and more intimate circle of trusted (clean-reliable) contacts.…”
Section: Accelerating Decelerating and Innovative Trendsmentioning
confidence: 99%
“…This paper assesses the distribution of household EnvFs across income groups in Germany in detail, focusing on the CF and MF. The case study of Germany enriches the literature in the income-specific household EnvFs, whose income inequality (Gini index 0.28) is lower than those of Spain (0.34) (López et al, 2016) and Japan (0.33) (Koide et al, 2019), but higher than that of Norway (0.26) (Steen-Olsen et al, 2016). Results and discussion on LF and WF are available in Supporting Information S1.…”
Section: Goal and Scope Of The Studymentioning
confidence: 78%
“…The Gini indices of the household income and CF in Spain are 0.34 and 0.12 (López et al., 2016), respectively. Despite having a higher income Gini index (0.32), Japan has a similar level of CF inequality (0.16) as Germany (Koide et al., 2019). The CF inequality in Spain might be lower due to the different heating requirements (Duarte et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A similar analysis can also be extended to quantify mitigation potentials from lifestyle changes in different consumer segments using survey microdata. Previous research based on survey microdata covering carbon footprints of households or consumer segments has revealed that they vary widely, even within-country, by from 3 to 10 times (Weber and Matthews 2008;Froemelt et al 2018;Koide et al 2019). This analysis approach is especially relevant considering the growing awareness of the inequalities, in terms of carbon footprints, between consumer and income segments globally and within each country, which underscores the urgency of addressing the emissions and footprints of high-carbon population segments (Kartha et al 2020;Ivanova and Wood 2020;UNEP 2020).…”
Section: Subnational Analysis Of Lifestyle Carbon Footprints and Lifestyle Changesmentioning
confidence: 99%